The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4049/jimmunol.1600846
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Human Skin Mast Cells in Dengue Virus Infection and Systemic Spread

Abstract: Dengue virus (DENV) is a mosquito-borne flavivirus that causes serious global human disease and mortality. Skin immune cells are an important component of initial DENV infection and systemic spread. Here, we show that mast cells are a target of DENV in human skin and that DENV infection of skin mast cells induces degranulation and alters cytokine and growth factor expression profiles. Importantly, to our knowledge, we also demonstrate for the first time that DENV localizes within secretory granules in infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 68 publications
(68 reference statements)
3
54
0
2
Order By: Relevance
“…Previous studies have demonstrated a dual role of mast cells in DENV pathophysiology by using mast cell-deficient mice, a role that is either protective by reducing vascular permeability or aggravative by enhancing DENV infectivity and macrophage skin infiltrates at the inoculation site compared to wild-type mice [20,21]. Troupin et al recently confirmed their crucial role in DENV replication and systemic propagation [22]. They demonstrated that human skin mast cells were permissive to DENV following exposure of samples of human skin tissue to infected mosquitoes [22].…”
Section: Figurementioning
confidence: 99%
“…Previous studies have demonstrated a dual role of mast cells in DENV pathophysiology by using mast cell-deficient mice, a role that is either protective by reducing vascular permeability or aggravative by enhancing DENV infectivity and macrophage skin infiltrates at the inoculation site compared to wild-type mice [20,21]. Troupin et al recently confirmed their crucial role in DENV replication and systemic propagation [22]. They demonstrated that human skin mast cells were permissive to DENV following exposure of samples of human skin tissue to infected mosquitoes [22].…”
Section: Figurementioning
confidence: 99%
“…Human skin mast cells were isolated and cultured as described previously (37,38). Briefly, mast cells were isolated and purified from fresh surgical specimens of human skin tissues that were purchased from the Cooperative Human Tissue Network (CHTN) of the National Cancer Institute.…”
Section: Cellsmentioning
confidence: 99%
“…The latter activates endothelial cell proliferation and is associated with increased vascular permeability. In addition, it has angiogenic and lymphogenic properties that together with the presence of viral particles in both cytoplasmic granules and granules after their release from mast cells, facilitate the systemic spread of the virus [39].…”
Section: Immune Response and Pathogenesis Of Dengue Virusmentioning
confidence: 99%